Perceptions on metrosexuality in men's tops in the Philippines - Britanico, Lyle Amelia M.; Elumba, Patricia Santos (2007)
Men's fashion is evolving because of the changes in attitude toward gender roles accompanied by changes in dress (Anspach 328). The phenomenon of metrosexuality along with Western designers, have inspired modern trends in men's fashions. Te study is about how metrosexuality as a fashion concept is viewed and perceived by men specifically for men's tops. The study aimed to determine perceptions of selected local respondents on metrosexuality in fashion and to determine details in men's tops considered as metrosexual style. Sampling of 560 male respondents, aged 21-27 years, working in Quezon City was done for the study. Data was obtained through survey questionnaires and a visual preference board. Perceptions on metrosexuality in men's wear were identified through he data gathered. Results of the study showed clothing which convey metrosexuality has mediocre or moderate acceptance from the respondents, which was evident with their preferred styles. Majority of the respondents characterize metrosexual styles as "bold, daring, fashion-forward and feminine". The results of the survey illustrated that selected respondents classify light and bright shades of red specifically fuchsia, pink and magenta as metrosexual. Light fabrics like stain and sheer fabrics, eye-catching fabrics such as leather, floral and bold stripped patterns, slim and tight-fitting tops were also considered as metrosexual details. One shoulder necklines not common to men's wear, turtleneck, upturned collars, fitted and rolled-up sleeves were identified as metrosexual as well. The study concluded that the elements of femininity and narcissism in the concept of metrosexuality by its definition, have categorized certain details in men's shits as metrosexual. These manifest in elaborate styles, conventionally female styles, daring and eye-catching details as well as contouring fit that give emphasis on the shape of the body. Metrosexuality has influenced the movement of men's fashion. This is evident in today's local market wherein metrosexuality has helped broaden the options of clothing for men. With the help of this study, fashion merchandisers can predict and understand the styles that are coming out of the men's fashion market today. This may also help in design strategies in men's wear in the fashion industry.
Thesis (BS Clothing Technology)--University of the Philippines Diliman.
Keywords: Men's clothing -- Philippines; Fashion -- Social aspects